Eco-marketing in industrial enterprise activities - N.M. Chupryna (Marketing i Menedžment Innovacij, 2015)
The aim of the article. The aim of the article is determination of the areas of industrial enterprise’s development and detection of the specificity of their activity in terms of environmental priorities. The results of the analysis. The analysis of the research and publications of the leading scholars on the eco-marketing’s problem was conducted. The main factors of eco-marketing’s mechanism use were considered. Eco-marketing was determined as an important tool of the enterprises’ modern production behavior correcting. Nowadays enterprises in Ukraine have to act according to modern production requirements, provide ecological safety and implement eco-marketing. The infrastructure of eco-marketing was built. The components of ecomarketing were distinguished. They are: eco-technologies, eco-product, eco-services, eco-consumers. The definition of «eco-consumer» was improved. The four areas of ecomarketing were identified: I – eco-services – eco-consumer; II – eco-Products – eco-consumer; III – eco-technologies – eco-product; IV – eco-technologies – eco-service. It was supposed that while analysing of the enterprise’s activities the influence of eco-marketing as a complex of influencing factors must be taken into consideration. Also it was determined that it is possibile to take into account the effect of «decoupling» in four areas of eco-marketing. The effect of «decoupling» was considered as an indicator of the region (the enterprise) transition to a green economy. It is proposed to calculate the effect of «decoupling» by means of an integral index. The main points of the mathematical set theory application for the analysis of the eco-marketing’s infrastructure components was allocated. It was supposed that the number of eco-consumers is set A, number of eco-products on the market is set B, the overall volume of eco-services in the area is set C and D is set that defines consumers which buy and consume not only eco-products and eco-services, but also other products. The graphic display of sets of eco-marketing components was provided. The need to phased the use of eco-marketing in industrial enterprises was approved. It can be proved due to the fact that the majority of industrial enterprises of Ukraine can not (both in terms of technology process, and need to attract sufficient number of resources, both material and non-materia), completely switch to producing of environmentally safe products and its promotion in the market. To apply eco-marketing and to display products it's necessary for the enterprise to implement marketing strategies. Based on these studies the matrix design of eco-marketing strategy was suggested. It was proved that selection of industrial enterprise eco-marketing strategy depends on the needs and interest of the products consumer (the interest of the consumer can be both psychological and physical). Conclusions and directions of further researches. As a result of the analysis, it was proposed to divide industrial enterprises on two types: environmentally dangerous and environmentally oriented. Industrial enterprises renovation and their modernization should be conducted considering environmental component. It will help to avoid an environmental catastrophe and use ecomarketing tools not only on the markets of industrial enterprise’s products.